PENERAPAN PENDEKATAN KOOPERATIF UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA DI KELAS 8A SMP NEGERI 2 KOPO KABUPATEN SERANG - Hermawan, Nurman (STAI Darul Qalam Tangerang, 2021)
The aim of this research is to improve Indonesian language learning achievement through the application of a cooperative approach in grade 8 A of SMP Negeri 2 Kopo in three cycles. Each cycle is once a meeting with a time of 150 minutes. The research was conducted by applying a cooperative approach in learning. The research data were taken using test, documentation and interview techniques. The research instrument used a learning result sheet and an observation sheet. Learning outcomes sheets are used to record quantitative data in the form of student learning outcomes before and after the cycle. The results showed that student learning outcomes increased from cycle to cycle. The increase in student learning outcomes was followed by an increase in student participation criteria from cycle to cycle. Actions in the first cycle can improve student learning outcomes to reach the good criteria reaching 53.50%. Actions in cycle II can improve the learning outcomes of all students achieving good criteria of 75.00%. Actions in cycle III can improve the learning outcomes of all students reaching the very good criteria of 92.50%. So there is no need to take action in the next cycle. Conclusion: the application of cooperative learning in Indonesian language learning can improve the quality of learning in Class 8A students of SMP Negeri 2 Kopo in the 2019-2020 academic year. This is indicated by an increase in the percentage of students who get learning outcomes with good criteria (score 4) and very good (score 5), ie from 0% (good) and 0% (very good). Cycle I: 53.50% (good) , Cycle II 75.00% (good). Cycle III: 92.50% (very good)